Increased efficiency in biomimetic Lewis acid-base pair catalyzed monoacylation of diols by acyl phosphate monoesters - Yuyang Li; Ronald Kluger (Canadian Science Publishing, 2017)
Acyl phosphate monoesters are biomimetic acylation reagents that require coordination to metal ions to react with cis-diol substrates in water. With lanthanide catalysts, outcomes are compromised by (1) the competitive lanthanide-promoted hydrolysis of the acyl phosphate reagents as well as by (2) the high affinity of lanthanum ions for the phosphate monoester by-product. Based on analysis of the mechanism of the process, optimizing reaction conditions can selectively inhibit the lanthanum-promoted hydrolysis of acyl phosphate monoesters. Furthermore, using zinc salts and lead salts in place of lanthanides enhances the reactivity of the reactants and causes less complexation of the metal ion with the by-products.